PERSEPSI SISWAPENDIDIKAN KEAHLIAN ADMINISTRASI PERKANTORAN (PKAP) TENTANG MANAJEMEN FASILITAS BELAJAR DI SMK NEGERI 2 KOTA BUKITTINGGI - JUWITA FRESCILLYA (Jurnal Bahana Manajemen Pendidikan, 2016)
This study aims to describe students’ perception aboutthe management of learning facilitiesat Sekolah Menengah Kejuruan Negeri (SMKN)2Bukittinggi. The population are426 people and sample are64 people, whch is determined by using purpossive sampling technique.Theinstrument that is used is questionnaire with  likert scale model. The data is analyzed by using mean score formula and continued with finding the percentage level of the students’ score achievement. The result of this study indicatesthat the management of learning facilitiesat SMKN 2 Bukittinggi iscategorizedadequate (77.42%).